Non-pharmacological treatments for pain relief in humanized birth assistance (Research, Society and Development, 2022)
Non-pharmacological treatments are one of the most viable alternatives in humanized childbirth care, due to the cost-effectiveness of their practice as well as the effectiveness of their use, although parturients have little knowledge of their existence. The aim of this study is to clarify the effectiveness of non-pharmacological treatments for pain in humanized childbirth. The study method is a literature review of the integrative literature review type, using 11 scientific articles. The results showed the effectiveness of using techniques such as Swiss Ball, Hydrotherapy, Music Therapy, Acupuncture, Breathing Exercises and Aromatherapy in pain relief and emotional control during labor. It is concluded that, in general, each of the methods has its effectiveness individually proven, but using the combination of several methods will bring with it greater efficiency, both of which can be used in different periods of pregnancy until conception of the fetus.